Pengaruh pasaran dan teknologi dalam ekonomi Malaysia: pendekatan input-output - Abdul Rashid, Zakariah; Mamat, Sahak; Ab. Rahman, Ab. Aziz; Gabil, Jeseel G. (Penerbit Universiti Kebangsaan Malaysia, 1999)
The industrial sector has played an important role in the development of the Malaysian economy. Each industry is related to the others and form a unified system, that harnesses primary inputs and converts them to final goods and services. However, the operation of transforming input to output is not that simple. Oil the supply side, the availability of resources and the type of technology would limit production. On the demand side, the extent and condition of market would affect the absorption of the products. In Malaysia and other developing economies, output growth is related to the absolute movements of raw materials, labour, capital and all other variables. The main objective of the study is to evaluate the effects of changing industrial production structure and changing level and composition of filial demand on intermediate input, labour and capital requirements of all industries in the Malaysian economy during 1978-87 period using an input-output analytical framework. Although these variables interact simultaneously, this study attempts to separate one effect from the other. The results of this study indicate that change in technology is neutral in the use of intermediate input, sparing in the use of labour and aggressive in the use of capital. On the other hand, change in the level and composition of final demand affects the use of inputs significantly.